2017
DOI: 10.1016/j.ypmed.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral lifestyle interventions for moderate and severe obesity: A systematic review

Abstract: Moderate and severe obesity (BMI ≥35 kg/m2) affect 15% of US adults, with a projected increase over the next two decades. This study reviews evidence of behavioral lifestyle interventions for weight loss in this population. We searched PubMed, PsychInfo, CINAHL®, and Scopus through February 2016 for experimental and quasi-experimental studies that tested a dietary and/or physical activity intervention with a behavioral modification component versus a comparator; and had ≥six-month follow-up and a weight-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 46 publications
2
75
0
2
Order By: Relevance
“…Although no significant differences were found between the groups, BMI was significantly reduced from T1 to T2 (p<0.017) for both groups. No significant reduction was found from T2 to T3, indicating that major weight loss does occur during the first weeks of PA, which was also confirmed by Lv et al [33]. Results indicate that major reductions in BMI are due to exercise and only minor changes by nutritional guidance.…”
Section: Changes In Bmisupporting
confidence: 77%
“…Although no significant differences were found between the groups, BMI was significantly reduced from T1 to T2 (p<0.017) for both groups. No significant reduction was found from T2 to T3, indicating that major weight loss does occur during the first weeks of PA, which was also confirmed by Lv et al [33]. Results indicate that major reductions in BMI are due to exercise and only minor changes by nutritional guidance.…”
Section: Changes In Bmisupporting
confidence: 77%
“…When it comes to weight loss interventions, it is well established that those interventions aiming at behavioral change towards different lifestyle components are the most effective [37]. In breast cancer survivors, recent systematic reviews have shown similar findings [38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a multifactorial approach to treating obesity is most effective, which includes combining treatment approaches. Individually, lifestyle/behavioural interventions have been shown to produce short‐term reductions in weight, while newer pharmacological approaches have received increasing support for their efficacy . More recently, endoscopic bariatric procedures have also shown promising metabolic outcomes .…”
Section: Psychological Outcomes Following Surgical and Endoscopic Barmentioning
confidence: 99%